An analysis of the S v Lotter and others judgment with reference to the defence of non-pathological criminal incapacity based on coercive persuasion - Carstens, Pieter Albert, 1960- (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.